The Role of Customer Satisfaction and Service Quality on Customer Loyalty: Case Study of M-Banking Services - I Wayan Gede Antok Setiawan Jodi; Sherry Adelia; Khamaludin; Prety Diawati; Ratnawita (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The cause of this look at is to investigate the direct impact of provider first-class on customer satisfaction of mobile banking customers, to analyze the direct effect of carrier exceptional on customer loyalty of cellular banking users, to investigate the direct effect of patron pleasure on purchaser loyalty of mobile banking customers and to analyze the indirect effect of carrier exceptional of client loyalty through consumer pleasure of bank BCA cell banking users. The population in this study is 1,050 customers using mobile banking. The sample in this study was taken purposively. The number of samples is 91 people. The studies device used on this study became a questionnaire or questionnaire that turned into made by means of the researcher himself. The studies device is a tool used to degree an observed natural or social phenomenon. The primary data used in this study is data obtained based on answers to questionnaires distributed to customers. The conclusion from the study is that there is a significant influence between service quality variables on customer satisfaction for customers who use mobile banking, so that improving the quality of online services will have an impact on customer satisfaction to use mobile banking. There is a significant influence between the variables of customer satisfaction on customer loyalty, the better the online service quality, the greater the loyalty level of mobile banking application users. There may be a sizeable have an impact on between the variables of customer delight on client loyalty, the higher the level of customer delight, the higher the level of loyalty of mobile banking application users